Analysis Of Nurse Workload On Implementation Of Patient Safety And Teamwork With Caring Behavior As Mediation Variables At Metro Hospitals Cikupa - Khodiyatussolihah Khodiyatussolihah; kemala Rita; Reza Hilmy (Syntax Corporation Indonesia, 2022)
The central issue of nursing is currently developing in the era of globalization and the era of hospital competition is the application of patient safety goals in hospitals. Most of the components of implementing the six patient safety goals are in the hands of nurses. Maintaining patient safety during treatment cannot be separated from the workload and caring attitude of a nurse who takes care of patients. Therefore, the authors want to examine the extent to which the workload and caring attitude of nurses and teamwork affect the application of patient safety. The main purpose of this study was to analyze the relationship between nurses' workload and teamwork on the application of patient safety goals and caring behavior as an intervening variable. The research population was inpatient and outpatient nurses with a sample number is 60 nurses. The research design uses quantitative data with a causative approach, with a focus on cause-and-effect relationships. Statistical methods for data analysis used in this study were univariate statistics, three-box methods, and path analysis to analyze the pattern of relationships between variables. The results showed: 1). Workload had a simultaneous effect on the variables of teamwork, caring behavior, and goals. patient safety in the hospital 2). Nurse workload has a positive effect on the variable implementation of patient safety goals. 3). The nurse's workload has a positive effect on the variable of the implementation of caring behavior. 4). Caring behavior has a positive effect on the variable of applying patient safety goals. 5). Nurse's workload has a positive effect on the teamwork variable 6). The teamwork variable did not significantly affect the variable implementation of patient safety goals.Conclusion: nurses' workload variables have a significant effect on teamwork, caring behavior, and patient safety goals. Caring behavior has a positive effect on patient safety goals, but teamwork does not significantly affect the implementation of patient safety goals.